1995
DOI: 10.1007/bf01322663
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane bound N-acetylneuraminic acid is involved in the infection of fibroblasts and phorbol-ester differentiated monocyte-like cells with human cytomegalovirus (HCMV)

Abstract: We focused on the role of membrane bound sugar residues in the infection of fibroblasts and monocyte-like cells with human cytomegalovirus (HCMV). Treatment of phorbol 12-myristate 13-acetate (PMA) differentiated monocyte-like cells THP-1 or human fibroblasts MRC-5 with lectins specific for N-acetylneuraminic acid (NeuAc) blocked infection with HCMV. HCMV failed to infect sialidase-treated differentiated THP-1 cells or MRC-5 cells. By using NeuAc, N-glycolylneuraminic acid (NeuGl) and alpha 2-3, but not alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The reason for this discrepancy is unclear, but it might be due to the difference in sugar derivatives, namely, an oligosaccharide and a GL. On the other hand, partial inhibitory activity of N-acetyllactosamine was also reported (Lobert et al, 1995), which is consistent with our results.…”
Section: Cfdisupporting
confidence: 93%
See 1 more Smart Citation
“…The reason for this discrepancy is unclear, but it might be due to the difference in sugar derivatives, namely, an oligosaccharide and a GL. On the other hand, partial inhibitory activity of N-acetyllactosamine was also reported (Lobert et al, 1995), which is consistent with our results.…”
Section: Cfdisupporting
confidence: 93%
“…Gangliosides, which are sialic acid-containing GLs, neither bound to HCMV nor inhibited infection. It was reported that sialyllactose (Neu5Acα2-3Galβ1-4Glc) had a weak inhibitory activity on HCMV infection (Lobert et al, 1995). The reason for this discrepancy is unclear, but it might be due to the difference in sugar derivatives, namely, an oligosaccharide and a GL.…”
Section: Cfdimentioning
confidence: 99%